Evolutionary optimization of interval mathematics-based design of a TSK fuzzy controller for anti-sway crane control - Smoczek, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
A hybrid method combining an evolutionary search strategy, interval mathematics and pole assignment-based closed-loop control synthesis is proposed to design a robust TSK fuzzy controller. The design objective is to minimize the number of linear controllers associated with rule conclusions and tune the triangular-shaped membership function parameters of a fuzzy controller to satisfy stability and desired dynamic performances in the presence of system parameter variation.
Keywords: interval mathematics; pole placement method; evolutionary algorithms; fuzzy logic; TSK controller; anti-sway crane control